The Killing Wind : A Chinese County's Descent into Madness During the Cultural Revolution - Hecheng, Tan (UK Oxford University Press, 2017)
In The Killing Wind, Tan recounts how over the course of 66 days in 1967, over 9,000 Chinese "class enemies" were massacred in the Daoxian.
Include Index
Keywords: Political violence -- China -- Cultural Revolution (China : 1966-1976)